X-ray crystallographic structure of a bacterial polysialyltransferase provides insight into the biosynthesis of capsular polysialic acid - Christian Lizak (Nature Portfolio, 2017)
Abstract Polysialic acid (polySia) is a homopolymeric saccharide that is associated with some neuroinvasive pathogens and is found on selective cell types in their eukaryotic host. The presence of a polySia capsule on these bacterial pathogens helps with resistance to phagocytosis, cationic microbial peptides and bactericidal antibody production. The biosynthesis of bacterial polySia is catalysed by a single polysialyltransferase (PST) transferring sialic acid from a nucleotide-activated donor to a lipid-linked acceptor oligosaccharide. Here we present the X-ray structure of the bacterial PST from Mannheimia haemolytica serotype A2, thereby defining the architecture of this class of enzymes representing the GT38 family. The structure reveals a prominent electropositive groove between the two Rossmann-like domains forming the GT-B fold that is suitable for binding of polySia chain products. Complex structures of PST with a sugar donor analogue and an acceptor mimetic combined with kinetic studies of PST active site mutants provide insight into the principles of substrate binding and catalysis. Our results are the basis for a molecular understanding of polySia biosynthesis in bacteria and might assist the production of polysialylated therapeutic reagents and the development of novel antibiotics.